Achievements and Prospects of Functional Pavement Materials and Structures - Zheng, Jian-long; You, Zhanping; Liu, Xueyan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In order to further promote the development of functional pavement technology, a Special Issue entitled "Achievements and Prospects of Functional Pavement" has been proposed by a group of guest editors. To achieve this objective, the articles included in this Special Issue are related to different aspects of functional pavements, including green roads to decrease carbon emissions, noise, and pollution, safety pavements to increase skid resistance through water drainage and snow removal, intelligent roads for monitoring, power generation, temperature control and management, and durable roads to increase service life with new theories, new design methods, and prediction models, as highlighted in this editorial.